Study of Acoustical Parameters in Some Binary Liquid Mixtures at 303K - Yadav, Ranjit Prasad (Academic Voices: A Multidisciplinary Journal, 2020)
This paper reports the experimental study of ultrasonic velocity, density and viscosity for binary liquid mixtures of methanol- bromobenzene and ethanol –bromobenzene at 3MHz ultrasonic frequency at 303k temperature. From these results, acoustic parameters such as adiabatic compressibility (β), free length () and acoustic impedance are calculated. This study is very useful to explain the nature of intermolecular interactions in the mixtures.